Immunotoxins and nanobody-based immunotoxins: review and update. (14th September 2021) - Khirehgesh, Mohammad Reza; Sharifi, Jafar; Safari, Fatemeh; Akbari, Bahman
Abstract: Immunotoxins (ITs) are protein-based drugs that compose of targeting and cytotoxic moieties. After binding the IT to the specific cell-surface antigen, the IT internalises into the target cell and kills it. Targeting and cytotoxic moieties usually include monoclonal antibodies and protein toxins with bacterial or plant origin, respectively. ITs have been successful in haematologic malignancies treatment. However, ITs penetrate poorly into solid tumours because of their large size. Use of camelid antibody fragments known as nanobodies (Nbs) as a targeting moiety may overcome this problem. Nbs are the smallest fragment of antibodies with excellent tumour tissue penetration. The ability to recognise cryptic (immuno-evasive) target antigens, low immunogenicity, and high-affinity are other fundamental characteristics of Nbs that make them suitable candidates in targeted therapy. Here, we reviewed and discussed the structure and function of ITs, Nbs, and nanobody-based ITs. To gain sound insight into the issue at hand, we focussed on nanobody-based ITs.